Genome-wide significant risk factors for Alzheimer’s disease: role in progression to dementia due to Alzheimer's disease among subjects with mild cognitive impairment - Lacour, A; Espinosa, A; Louwersheimer, E; Heilmann, S; Hernández, I; Wolfsgruber, S; Fernández, V; Wagner, H; Rosende-Roca, M; Mauleón, A; Moreno-Grau, S; Vargas, L; et al. (Molecular psychiatry, 2017)
Few data are available concerning the role of risk markers for Alzheimer’s disease (AD) in progression to AD dementia among subjects with mild cognitive impairment (MCI). We therefore investigated the role of well-known AD-associated single-nucleotide polymorphism (SNP) in the progression from MCI to AD dementia. Four independent MCI data sets were included in the analysis: (a) the German study on Aging, Cognition and Dementia in primary care patients ( n =853); (b) the German Dementia Competence Network ( n =812); (c) the Fundació ACE from Barcelona, Spain ( n =1245); and (d) the MCI data set of the Amsterdam Dementia Cohort ( n =306). The effects of single markers and combined polygenic scores were measured using Cox proportional hazards models and meta-analyses. The clusterin ( CLU ) locus was an independent genetic risk factor for MCI to AD progression ( CLU rs9331888: hazard ratio (HR)=1.187 (1.054–1.32); P =0.0035). A polygenic score (PGS1) comprising nine established genome-wide AD risk loci predicted a small effect on the risk of MCI to AD progression in APOE- ɛ4 (apolipoprotein E-ɛ4) carriers (HR=1.746 (1.029–2.965); P =0.038). The novel AD loci reported by the International Genomics of Alzheimer's Project were not implicated in MCI to AD dementia progression. SNP-based polygenic risk scores comprising currently available AD genetic markers did not predict MCI to AD progression. We conclude that SNPs in CLU are potential markers for MCI to AD progression.